Developing a Spatial Framework for Ship Vulnerability Assessment Based on Category Theory - Ramezani, Abouzar; Malek, Mohammad Reza (Journal of ship research, 2023)
Ships vulnerability analysis is one of the most important issues in today’s research, to reduce damage and increase safety. To increase the safety of ships, the effective parameters of the vulnerability of ships, the impact of each of them, and the relationship between these parameters should be identified to formulate different scenarios to analyze the vulnerability of ships. This process leads to the formation of simulation models to assess the risk of vessels. The creation of a spatial conceptual framework is needed to create integrated vulnerability models. The most important innovation of this research is the development of a spatial framework for analyzing ships’ vulnerability based on category theory. A framework that can be used to model the various scenarios of ships’ vulnerability from a variety of perspectives. To provide this framework, objects, operators, relationships, and assumptions for vulnerability analysis have been developed. To better express and convey the concepts, the spatial framework of the vulnerability analysis is presented in the form of category theory, which is a mathematical structure. The category theory is a good tool for expressing and creating a mathematical structure for objects and complex relationships in the real world, where other tools do not have this ability. The benefits of the built-in framework have been described with an integrated, precise mathematical structure that can be generalized to other subjects. Studies show that the developed framework is capable of modeling different scenarios for vulnerability analysis to find the best solution to reduce vulnerability.